Հոգևոր տաղերգության նմուշների Կոմիտասյան գրառումները - Մուշեղյան, Աստղիկ (Մատենադարան)
One of the most important parts of the creative heritage of Komitas Vardapet is the samples of Armenian sacred music, particularly the taghs, recorded by him. Our work examines some of them: Where art thou, my Mother?, The Angel Exclaimed, On the First Day of the Week and Mary Magdalene. Issues related to their subject matter, authorship, time and place of creation as well as the characteristic features of musical components, melodic styles and the construction of a musical composition are discussed. An analysis of intonation-rhythmic structures, modal characteristics etc. has been carried out. The taghs presented in the article are of great artistic value and belong to the best examples of Armenian tagh art.. Важнейшей частью творческого наследия Комитаса Вардапета являются записанные им образцы армянского духовного песнетворчества, в частности моя?», «Ангел восклицал», «В первый день недели» и «Мария Магдалина». Рассматриваются вопросы, связанные с их тематикой, авторством, временем и местом со- здания. Выявлются характерные особенности музыкальных компонентов, мелодических стилей, построения музыкальной композиции. Проводится анализ интонационноритмических структур, ладовых особенностей и т. д. Представленные в статье таги имеют большую художественную ценность и принадлежат к лучшим образцам армянского тагового искусства.
Keywords: Երաժշտագիտություն